Determinan Penggunaan Metode Kontrasepsi Jangka Panjang Di Indonesia (Analisis SDKI 2017) - Husnul Khatimah; Yunita Laila Astuti; Vini Yuliani (Yayasan Literasi Sains Indonesia, 2022)
Effective contraception such as the Long-acting reversible contraceptives can prevent one in every three maternal deaths by allowing women to arrange births, avoid unwanted pregnancies and abortions, and stop giving birth when they have reached the desired family size. This study aimed to determine the factors associated with long-acting reversible contraceptives methods in Indonesia. This study used secondary data by analyzing the results of the Indonesian Demographic and Health Survey (IDHS) in 2017. The sample was married women aged 15-19 years with a total of respondents being 19522. This study showed, that the most types of contraception used by respondents were short-acting contraceptive methods (pills and injections), namely 75.4%, and only 24.6% of respondents used long-acting reversible contraceptives. The results of the multivariate analysis described the determinants of long-acting reversible contraceptives were age, parity, occupation, cost of family planning, and decision-maker. It is necessary to improve counseling services and promote the long-acting reversible contraceptives as effective contraception in delaying birth, considering that most of the respondents used long-acting reversible contraceptives when they were >35 years old with grand multipara. In addition, decision-making by respondents and their partners as well as health workers as service providers is also very influential in increasing the use of long-acting reversible contraceptives so effective counseling and involving partners is also important.